The Factors that Influence Earnings Management: Evidence on Basic Materials Sector - Kurnia, Kurnia; Dary, Putri Wulan (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Earnings management is an action to modify accounting records so that there is intervention in the financial statements while complying with applicable accounting standards. This study aims to determine the relationship between earnings management with tax incentives, tax avoidance, and financial distress in basic materials sector companies listed on the Indonesia Stock Exchange for the period 2016 – 2021. This research can suggest the companies or investors regarding the factors that influence earnings management practices in a company so that it can be more efficient in making business decisions in order to maintain the stability of the company. The sample selection technique in this study used purposive sampling. The resulting samples were 13 companies and 78 observational data. The analysis technique used is panel data regression using Eviews 12 software. The results show that tax incentives, tax avoidance, and financial distress simultaneously affect earnings management. Partially tax incentives have a negative influence on earnings management, while tax avoidance and financial distress have a positive influence on earnings management.